Dismantling and reorganizing Pseudomonas marginalis sensu lato. (28th December 2022) - Sawada, Hiroyuki; Fujikawa, Takashi; Satou, Mamoru
Abstract: Until recently, it had been a common practice in the field of plant disease control to identify bacterial strains with the following characteristics as Pseudomonas marginalis : fluorescent; oxidase‐, potato soft rot‐ and arginine dihydrolase‐positive; soft rot‐causing (here referred to as P . marginalis sensu lato). In contrast, as phylogenetic and genomic analyses have been introduced into the bacterial taxonomy, it became clear that P . marginalis sensu lato is heterogeneous, suggesting that it might be a species complex containing many cryptic species. Therefore, a preliminary survey was performed targeting the P . marginalis sensu lato strains preserved in the NARO (National Agriculture and Food Research Organization, Japan) Genebank to sort these into strains corresponding to P . marginalis sensu stricto (i.e., strains that would be included in the same species range as the type strain of P . marginalis ) and strains that might not fit this category. Since then, attempts have been made to examine the taxonomic affiliations of the latter by using a polyphasic approach. As a result, some strains were proven to differ from any known species and are described as the following novel species: Pseudomonas kitaguniensis, Pseudomonas allii, Pseudomonas cyclaminis, Pseudomonas petroselini, Pseudomonas brassicae, Pseudomonas lactucae, Pseudomonas aegrilactucae and Pseudomonas morbosilactucae . In this article, the profiles of each of these novel species and a scheme for their identification are briefly introduced. In addition to the problem of cryptic species, reorganizing P . marginalis sensu lato still faces various challenges, which we discuss. Abstract : Pseudomonas marginalis sensu lato identified based on a small number of phenotypic characteristics has been found to be a species complex containing many cryptic species and is currently being divided into multiple novel species.